Polyimide film, its manufacturing method, and flexible device
The polyimide film with fluorine and ether groups, imidated under specific conditions, addresses the challenges of reduced transparency and mechanical weakness in conventional polyimide films, achieving high heat resistance and stability for flexible device applications.
Patent Information
- Application Number
- JP2020211439
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-12-21
AI Technical Summary
Conventional polyimide films used in flexible devices face challenges such as reduced transparency, mechanical weakness, and discoloration when exposed to high temperatures, which limits their application in extreme heat-resistant processes.
A polyimide film with a fluorine atom and an ether group is developed, which is imidated under specific heat treatment conditions to achieve a film with high transparency, heat resistance, and peelability from a support substrate, while maintaining low residual solvent levels and high tensile elongation.
The resulting polyimide film exhibits excellent light transmittance, extreme heat resistance, and stability against discoloration even at high temperatures, making it suitable for flexible devices requiring transparency and durability, such as organic EL devices and touch panels.
Smart Images

Figure 0007657048000001 
Figure 0007657048000002 
Figure 0007657048000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide film useful as a transparent film material or a transparent flexible substrate material, and in particular to a transparent resin substrate material having high transparency, little discoloration during high-temperature processing, no polyimide swelling, high heat resistance, and lift-off properties, and a flexible device using the same. [Background technology]
[0002] 2. Description of the Related Art Display devices such as liquid crystal display devices and organic electroluminescence (EL) devices, as well as touch panels, are used as components of various displays, including large displays such as televisions, and small displays for mobile phones, personal computers, and smartphones. For example, an organic EL device is generally produced by forming a thin film transistor (TFT) on a glass substrate, which is a supporting base material, and then forming an electrode, a light-emitting layer, and another electrode on the TFT in that order, and then hermetically sealing them with a glass substrate, a multilayer thin film, etc. Also, a touch panel is constructed by bonding a first glass substrate on which a first electrode is formed and a second glass substrate on which a second electrode is formed via an insulating layer (dielectric layer).
[0003] In other words, these components are laminates in which various functional layers such as TFTs, electrodes, and light-emitting layers are formed on a glass substrate. By replacing this glass substrate with a resin substrate, components using conventional glass substrates can be made thinner, lighter, and more flexible. This is expected to be used to obtain flexible devices such as flexible displays. On the other hand, resins are inferior to glass in terms of dimensional stability, transparency, heat resistance, moisture resistance, and film strength, and various studies are being conducted.
[0004] Polyimide is one of the promising resin substrate materials because of its excellent heat resistance and dimensional stability. In particular, polyimides having fluorine atoms in the polyimide structure (fluorine-containing polyimides) and polyimides having an alicyclic structure (alicyclic polyimides) have excellent transparency and are expected to be applied to flexible devices that require transparency, such as substrates for organic electroluminescence devices, touch panel substrates, and color filter substrates.
[0005] Transparent polyimide substrates for flexible devices can be obtained by forming a transparent polyimide film on a glass substrate, mounting electronic components on the transparent polyimide film, and then peeling off the substrate. Fluorine-containing polyimides have excellent peelability from glass substrates, so they are particularly expected to be used for transparent polyimide substrates.
[0006] For example, Patent Document 1 discloses a fluorine-containing polyimide film for flexible devices produced by peeling it off from a carrier substrate, which has a glass transition temperature of 300° C. or higher, a thermal decomposition temperature of 500° C. or higher, and a thermal expansion coefficient of 20 ppm / K or lower. However, no consideration is given to transparency. Patent Document 2 discloses a laminate consisting of an inorganic substrate and a polyimide film obtained by casting a fluorine-containing polyimide precursor solution on the inorganic substrate, followed by drying and imidization, which has high total light transmittance and low outgassing (0.3% or less). Here, outgassing is defined as the thermal weight loss rate at 300°C. In addition, Patent Document 2 discloses that in order to reduce outgassing, it is effective to increase the heating temperature during imidization, but there is a tendency for the haze to increase and the total light transmittance to decrease due to the crystallinity and coloring of the polyimide, and in particular, when the maximum temperature exceeds 400°C, whitening becomes noticeable due to the crystallization of the polyimide. Conversely, it discloses that if heating is performed at a relatively gentle temperature to suppress the decrease in transparency and coloring, the outgassing cannot be reduced, and the imidization does not proceed sufficiently, and the mechanical strength of the polyimide tends to be insufficient. In other words, it can be said that there is a trade-off between heat resistance and transparency. Here, it discloses that it is necessary to appropriately set the heating temperature and heating time as an effective method for reducing outgassing without impairing transparency. However, since the above-mentioned problems such as crystallinity and coloring have been suggested, heat resistance in a high temperature range exceeding 400°C has not been examined. One of the components of outgassing is residual solvent in the polyimide film. If there is an excessive amount of residual solvent, it may cause peeling between the polyimide film and the barrier layer during the manufacturing process of flexible devices.
[0007] Patent Documents 3 and 4 disclose fluorine-containing polyimides having specific tetracarboxylic dianhydrides, which are excellent in heat resistance and transparency. These fluorine-containing polyimides also have a light transmittance of 80% or more at 400 nm in a film state and a thermal expansion coefficient of 20 ppm / K or less. On the other hand, the 5% weight loss temperature is less than 500°C.
[0008] Patent Document 5 discloses a specific polyimide with excellent thermal decomposition temperature and transparency. It is formed into a film (imidized) at 430°C, but does not disclose the glass transition temperature (Tg). The polyimide described in Patent Document 5 is considered to require a specific alicyclic structure, so the Tg is expected to be 400°C or lower. In other words, the polyimides disclosed in Patent Documents 2 to 5 do not have sufficient heat resistance from the viewpoint of application to applications and processes that require extremely high heat resistance due to high-temperature heat treatment, such as a manufacturing process for TFT substrates for flexible OLEDs, and a manufacturing process for TFT substrates and CF substrates for flexible LCDs.
[0009] Patent Document 6 discloses a polyimide film having fluorine atoms, which has excellent transparency, extremely high heat resistance, and is easily peeled off from a supporting substrate. However, there is room for improvement in terms of maintaining transparency when heat-treated at high temperatures. In addition, there is a problem that the polyimide film is easily torn during the above-mentioned manufacturing process due to insufficient mechanical strength and elongation. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2010-202729 A [Patent Document 2] JP 2012-40836 A [Patent Document 3] JP 2015-28143 A [Patent Document 4] JP 2016-74915 A [Patent Document 5] Patent No. 6443579 [Patent Document 6] JP 2019-178269 A Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, an object of the present invention is to provide a polyimide film which is extremely useful as a transparent polyimide substrate material, having excellent transparency, extremely high heat resistance, and easy peeling from a supporting substrate, which was difficult to achieve with conventional techniques, and which has little residual solvent so that peeling between the polyimide film and the barrier layer does not occur, has high tensile elongation so that it is unlikely to break during the production process, etc., and shows little discoloration even when heated at high temperatures, and a flexible device using the same. [Means for solving the problem]
[0012] Therefore, as a result of intensive research, the present inventors have found that a polyimide film that solves the above-mentioned problems can be obtained by imidizing a specific polyimide having a fluorine atom and an ether group (bond) under specific heat treatment conditions to form a film, and have thus completed the present invention.
[0013] That is, the present invention provides a polyimide film having a fluorine atom and an ether group in a polyimide structure, Residual solvent is 500 ppm or less, The polyimide film has a yellowness index of 15 or less and a tensile elongation of 15% or more, and further has a yellowness index of 20 or less and a tensile elongation of 13% or more after heating at 420°C for 30 minutes.
[0014] Here, the polyimide film of the present invention preferably has an average thickness of 5 to 50 μm, a yellowness index of 15 or less when converted into a 10 μm-thick film, and even after heating at 420° C. for 30 minutes, a yellowness index of 20 or less when converted into a 10 μm-thick film.
[0015] The polyimide film of the present invention preferably has a glass transition temperature of 400° C. or higher.
[0016] In addition, in the polyimide film of the present invention, the total amount of the structural units derived from a diamine having an ether group and / or the structural units derived from a tetracarboxylic dianhydride having an ether group is preferably 10 mol % or more based on the total amount of the structural units derived from a diamine and the structural units derived from a tetracarboxylic dianhydride.
[0017] In the polyimide film of the present invention, the structural units derived from diamine represented by the following formula (1) or (2) preferably account for 50 mol % or more of all the structural units derived from diamine. [ka] [ka] [Here, R1 to R8 in formula (1) or formula (2) are each independently a hydrogen atom, a fluorine atom, an alkyl or alkoxy group having 1 to 5 carbon atoms, or a fluorine-substituted hydrocarbon group, and at least one of R1 to R4 in formula (1) and at least one of R1 to R8 in formula (2) is a fluorine atom or a fluorine-substituted hydrocarbon group.]
[0018] The present invention also provides a flexible device comprising the above-mentioned polyimide film and a functional layer laminated on the surface thereof.
[0019] The present invention also relates to a method for producing a polyimide film, comprising the steps of: applying a polyamic acid solution having a fluorine atom and an ether group onto a supporting substrate so that the average thickness of the polyimide after curing is 5 to 50 μm; and then heat-treating the solution at a maximum temperature of 390 to 470° C. to imidize the solution, thereby forming a polyimide film. Effect of the Invention
[0020] The polyimide film of the present invention has both excellent light transmittance and extremely high heat resistance. In addition, there is little residual solvent, and the polyimide film and the barrier layer thereon do not peel off during processing. In addition, the tensile elongation of the film is high, and the film does not break during processing. Furthermore, even when heated at high temperatures, the film does not discolor much, and shows stable optical properties for forming multiple layers during processing. Therefore, it can be applied to flexible devices that require transparency, such as substrates for organic EL devices, touch panel substrates, and color filter substrates. For example, it can be used in the process of forming TFT substrates and CF substrates for flexible LCD applications. Furthermore, it can be suitably used for flexible devices that require extremely high heat resistance, such as the process of forming TFT substrates for flexible OLED applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The present invention will now be further described. As an example, the polyimide film of the present invention can be produced by polymerizing raw materials, diamine and tetracarboxylic dianhydride (hereinafter also simply referred to as "acid dianhydride"), in the presence of a solvent to obtain a polyamic acid solution, which is then applied to a supporting substrate and imidized by heat treatment. Alternatively, the polyimide film can be produced by applying a polyimide solution to a supporting substrate and drying by heat treatment. The molecular weight of the polyimide film can be controlled mainly by changing the molar ratio of the raw materials diamine and acid dianhydride, which can be adjusted to 0.980 to 1.025. The weight average molecular weight (Mw) is preferably adjusted to the range of 80,000 to 800,000.
[0022] The polyamic acid solution is prepared by first dissolving a diamine in an organic solvent, then adding an acid dianhydride to the solution to produce a polyamic acid, which is a polyimide precursor. For example, the polyamic acid solution is obtained by dissolving a diamine in an aprotic amide solvent such as N,N-dimethylacetamide or N-methyl-2-pyrrolidone under a nitrogen stream, then adding an acid dianhydride and reacting at room temperature for about 3 to 120 hours. When adding the monomer, it is better to heat the mixture at 30 to 50°C for 2 to 10 hours in order to dissolve the monomer more quickly. In addition, the molecular end may be blocked with an aromatic monoamine or an aromatic monocarboxylic anhydride. Examples of the organic solvent include N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethylformamide, n-methylpyrrolidinone, 2-butanone, diglyme, xylene, butyrolactone, and triethylene glycol dimethyl ether, and these may be used alone or in combination of two or more.
[0023] When the obtained polyamic acid solution is applied to a supporting substrate, the viscosity of the solution is preferably adjusted to a range of 1,000 to 50,000 cps (=cP) by adjusting the concentration and Mw of the polyamic acid. If the viscosity is high, it is sufficient to dilute the solution by adding a solvent.
[0024] Furthermore, the surface of the supporting substrate to which the polyamic acid solution is to be applied may be appropriately treated before application.
[0025] After the polyamic acid solution is applied, the support substrate is heat-treated to imidize the polyamic acid and form a polyimide film. The conditions of the heat treatment in the imidization step are not particularly limited as long as the polyimide film obtained is a polyimide film having fluorine atoms and ether groups in the polyimide structure, has a residual solvent of 500 ppm or less, a tensile elongation of 15% or more, a yellowness index of 15 or less, and after heating at 420°C for 30 minutes, the yellowness index is 20 or less and the tensile elongation is 13% or more. Preferably, the maximum temperature of the heat treatment (hereinafter referred to as "maximum imidization temperature") is 390 to 470°C. The lower limit of the maximum imidization temperature is more preferably 400°C. The upper limit of the maximum imidization temperature is more preferably 450°C. If the maximum imidization temperature is within this range, a polyimide film having extremely excellent heat resistance while maintaining excellent transparency can be obtained, especially when the polyimide film uses a fluorine-containing and ether group polyimide. When the maximum imidization temperature is less than 390°C, the amount of remaining solvent is large, and the glass transition temperature tends to be low. On the other hand, when the maximum temperature exceeds 470°C, the transmittance in the visible light region decreases, and the yellowness index (YI) tends to increase. The holding time at the maximum temperature varies depending on the heating method, the heat capacity of the support substrate, the thickness of the polyimide film, etc., but is preferably 1 minute to 3 hours. If it is less than 1 minute, the effect of the heat treatment at that temperature is small, and if it exceeds 3 hours, excessive heat is applied, particularly when the maximum imidization temperature is 400°C or higher, and the transmittance in the visible light region decreases, and the YI tends to increase.
[0026] In addition, imidization can be performed under any conditions, such as in air, under low oxygen concentration, in an inert gas atmosphere, under reduced pressure, or under vacuum, but from the viewpoint of reducing the YI, it is preferable to perform imidization under an oxygen concentration of 10% or less, more preferably 5% or less, and even more preferably 3% or less. Conditions other than the maximum temperature in the imidization step, such as the rate of temperature rise, can be appropriately adjusted depending on the properties and amount of the organic solvent contained in the polyamic acid solution and the structure of the polyamic acid.
[0027] Prior to imidization, the polyamic acid solution may be dried at 200°C or less for 2 to 60 minutes to volatilize the organic solvent contained in the polyamic acid solution. For example, the polyamic acid solution is applied onto a support substrate using an applicator, pre-dried at 150°C or less for 3 to 60 minutes, and then the above-mentioned heat treatment is performed to remove the solvent and imidize. In addition, in order to evaporate the remaining solvent, the solution may be heated to a temperature above the boiling point, for example, at a temperature in the range of 300 to 400°C for 2 to 60 minutes. In order to stabilize the molecular structure rearranged at the maximum temperature, it is preferable to lower the temperature gradually over a period of time when lowering the temperature from the maximum temperature to room temperature, and it is preferable to return the temperature to room temperature over a period of 3 hours or more.
[0028] The coating method may be a known method, but is preferably a spin coating method or a slit coater method.
[0029] In addition, in the heat treatment, chemical imidization can be carried out by adding a dehydrating agent and a catalyst to the polyamic acid solution and reacting them.
[0030] The supporting substrate may be any known substrate without limitation, but is preferably glass, stainless steel (SUS), aluminum, copper foil, or polyimide film, more preferably glass, because of its smoothness, high heat resistance, and small dimensional change rate. The thickness of the supporting substrate is preferably, for example, about 20 μm to 1.0 mm.
[0031] The polyimide film of the present invention obtained by the above heat treatment has a low residual solvent content, high tensile elongation, low yellowness index, and does not discolor even when heated at high temperatures. Specifically, the residual solvent content is 500 ppm or less, the tensile elongation is 15% or more, and the yellowness index is 15 or less. In addition, after heating at 420°C for 30 minutes, the yellowness index is 20 or less and the tensile elongation is 13% or more.
[0032] The polyimide film of the present invention has a residual solvent content of 500 ppm or less, and the content of the residual solvent is extremely low. Therefore, when used as a TFT substrate, the high-temperature process of 400 to 500°C when the barrier layer and the organic EL layer are formed may cause the barrier layer to swell and peel off due to the generation of residual solvent from the polyimide film, but this can be suppressed as much as possible. Furthermore, within the scope of the present invention, by setting the maximum imidization temperature during film formation to a preferred condition of 390°C or more, the residual solvent can be reduced to 300 ppm or less, and by setting the more preferred condition to 150 ppm or less.
[0033] The temperature rise conditions during film formation can be appropriately selected. For example, a method of raising the temperature to the imidization temperature at a constant heating rate and holding it for a constant time; a two-step curing method of holding the temperature at 300-400°C, which is a temperature range higher than the boiling point of the solvent, for a constant time, then raising the temperature to the imidization temperature again and holding it at the maximum temperature for a constant time; a three-step curing method in which a constant holding time is set between 100-200°C in the two-step curing so that the solvent can be slowly evaporated; and a two-step curing method in which the temperature is raised to 350°C-400°C in the first step, held at the maximum temperature for a constant time, then lowered to room temperature, and then raised from room temperature again at a constant heating rate to a temperature higher than the first step, and held at the maximum curing temperature for a constant time. In the case of stepwise heating, the temperature may be raised slowly at a speed of 4°C / min or less in order to remove as much solvent as possible in the low temperature range, and raised at a faster speed of 4°C / min or more in order to maintain transparency in the high temperature range.
[0034] The polyimide film of the present invention has a tensile elongation of 15% or more, so it will not break during the manufacturing process, and when used as a flexible display, it also has excellent foldability. Since it has such a tensile elongation, for example, after a functional layer such as a display element is formed on the surface of the polyimide film, in the laser lift-off process in which the polyimide film is peeled off from the glass (supporting substrate), the polyimide film can be peeled off cleanly from the glass without breaking, which is preferable. Preferably, the tensile elongation is 20% or more.
[0035] In addition, since the polyimide film of the present invention has a YI of 15 or less, it can be suitably used for substrates that require transparency and little coloration, such as TFT substrates for organic EL devices, touch panel substrates, color filter substrates, etc. Furthermore, by setting the type and component ratio of the structural units derived from the acid dianhydride and diamine in the polyimide component range of the present invention to preferred conditions, it can be made 13 or less. By setting it in such a range, the visibility of the substrate is further improved. The polyimide film of the present invention preferably has an average thickness of 5 to 50 μm. A more preferred lower limit is 7 μm. On the other hand, a more preferred upper limit is 30 μm, and even more preferred is 20 μm. The average thickness may be measured, for example, according to the method described below. The YI preferably satisfies the above range as the YI converted into a film thickness of 10 μm.
[0036] The polyimide film of the present invention has a yellowness index of 20 or less and a tensile elongation of 13% or more even after heating at 420° C. for 30 minutes. Therefore, even when heat treatment at 400° C. or more is performed in the manufacturing process of a TFT substrate for flexible OLED use, a TFT substrate for flexible LCD use, or a CF substrate, the polyimide film does not discolor and is not easily torn. As described above, the YI after this heat treatment preferably satisfies the above range as the YI converted to a film thickness of 10 μm.
[0037] In addition, since the polyimide film of the present invention has a glass transition temperature of 400°C or more, it has an advantage that the polyimide film is unlikely to deteriorate even when heat treatment at 400°C or more is performed in the manufacturing process of a TFT substrate for flexible OLED, a TFT substrate for flexible LCD, or a CF substrate.
[0038] The structure of the polyimide film satisfying the above-mentioned performance is not limited as long as it is a polyimide containing fluorine and an ether group (bond), but it is preferable that the structural unit containing an ether group is 10 mol% or more of the total structural units. Since the polyimide having an ether group has excellent adhesion to the substrate, it can be suppressed from peeling off from the substrate during the process. In addition, the bond dissociation energy of the ether group is larger than that of the -C- bond, so it is difficult to decompose thermally, and discoloration due to thermal decomposition is unlikely to occur even when heated at high temperatures. Therefore, even when heat treatment is performed at 400°C or more in the manufacturing process of the TFT substrate for flexible OLED, the TFT substrate for flexible LCD, and the CF substrate, the polyimide film does not discolor, and has the advantage that it is difficult to peel off and tear.
[0039] The structure of the polyimide film satisfying the above-mentioned performance is not limited as long as it has a fluorine atom and an ether group in the polyimide structure. However, in order to obtain excellent heat resistance, the polyimide component constituting the polyimide film preferably contains structural units represented by the following formulas (1) and (2) as structural units derived from a diamine.
[0040] [ka]
[0041] [ka]
[0042] In the above formula (1) or (2), R1 to R8 are each independently a hydrogen atom, a fluorine atom, an alkyl group or an alkoxy group having 1 to 5 carbon atoms, or a fluorine-substituted hydrocarbon group, and at least one of R1 to R4 in formula (1) and at least one of R1 to R8 in formula (2) is a fluorine atom or a fluorine-substituted hydrocarbon group. The fluorine atom or the fluorine-substituted hydrocarbon group may be contained only in the structural unit derived from the diamine, or may also be contained in the structural unit derived from the acid dianhydride.
[0043] Preferred specific examples of R1 to R8 include -H, -CH3, -OCH3, -F and -CF3, and more preferably, at least one of R1 to R8 is either -F or -CF3.
[0044] Preferred structural units derived from diamines and represented by the above formula (1) or (2) include structural units represented by i to x in the following formula (4).
[0045] [ka]
[0046] Among the above formula (4), formula (4)-viii, which is a structural unit formula derived from 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (abbreviation: TFMB), is more preferable.
[0047] The polyimide film of the present invention contains one or more of the diamine-derived structural units represented by the above formula (1) or (2) in an amount of preferably 50 mol % or more, more preferably 70 mol % or more, even more preferably 80 mol % or more, and even more preferably 90 mol % or more of all diamine-derived structural units. Within this range, by setting the maximum temperature in the heat treatment for imidization to 390° C. to 470° C., it is possible to develop particularly high heat resistance while maintaining high transparency and excellent peelability from the supporting substrate.
[0048] From the viewpoints of achieving good thermochromic properties, excellent adhesion to a substrate, and high tensile elongation, the total of the structural units derived from a diamine having an ether group and / or the structural units derived from a tetracarboxylic dianhydride having an ether group is preferably 10 mol % or more, more preferably 15 mol % or more, and even more preferably 20 mol % or more, based on the total of the structural units derived from the diamine and the structural units derived from the tetracarboxylic dianhydride.
[0049] Examples of structural units derived from diamines having an ether group include 4,4'-diaminodiphenyl ether (4,4'-DAPE), 3,3-diaminodiphenyl ether, bis(p-β-amino-t-butylphenyl) ether, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis(3-aminophenoxy)benzene (APB), 1,3-bis(4-aminophenoxy)benzene (TPE-R), and 1,4-bis(4-aminophenoxy)benzene. More preferably, 4,4'-diaminodiphenyl ether (4,4'-DAPE), 1,3-bis(3-aminophenoxy)benzene (APB), 1,3-bis(4-aminophenoxy)benzene (TPE-R), and 1,4-bis(4-aminophenoxy)benzene.
[0050] The structural units derived from tetracarboxylic dianhydrides having ether groups include 4,4'-oxydiphthalic dianhydride (ODPA), bis(2,3-dicarboxyphenyl)ether dianhydride, 5,5'-bis(trifluoromethyl)-3,3',4,4'-tetracarboxydiphenyl ether dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}diphenyl ether dianhydride, bis{3,5-di(trifluoromethyl)phenoxy}pyromellitic dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}benzene dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}, bis(dicarboxylic acid dianhydride, bis(trifluoromethyl)dicarboxyphenoxy) bis(dicarboxyphenoxy)trifluoromethylbenzene dianhydride, bis(dicarboxyphenoxy)bis(trifluoromethyl)benzene dianhydride, bis(dicarboxyphenoxy)tetrakis(trifluoromethyl)benzene dianhydride, 2,2-bis{(4-(3,4-dicarboxyphenoxy)phenyl}hexafluoropropane dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}biphenyl dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}bis(trifluoromethyl)biphenyl dianhydride, bis(dicarboxyphenoxy)bis(trifluoromethyl)biphenyl dianhydride, and the like.
[0051] The structural unit derived from the diamine having an ether group and / or the structural unit derived from the tetracarboxylic dianhydride having an ether group may contain two or more of the above. Among these, 4,4'-DAPE, APB, TPE-R and ODPA are more preferable, and ODPA is even more preferable.
[0052] The diamine-derived structural unit may include a known diamine-derived structural unit other than the structural unit represented by the above general formula (1) or (2) and the diamine-derived structural unit having an ether group.
[0053] The structural units derived from the known diamines are preferably 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,6-dimethyl-m-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, 2,4-diaminomesitylene, 4,4'-methylenedi-o-toluidine, 4,4'-methylenedi-2,6-xylidine, 4,4'-methylene-2,6-diethylaniline, 2,2 ...di-2,6-diethylaniline, 2,2'-dimethyl-4,4'-diaminobiphenyl, 4,4'-diaminodiphenyl ether, 4,6-dimethyl-m-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, 2,4-diaminomesitylene, 4,4' ,4-toluenediamine, m-phenylenediamine, p-phenylenediamine, 4,4'-diaminodiphenylpropane, 3,3'-diaminodiphenylpropane, 4,4'-diaminodiphenylethane, 3,3'-diaminodiphenylethane, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfide, 3,3'-diaminodiphenylsulfide, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, 4,4'-diaminobiphenyl phenyl, 3,3'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 4,4'-diamino-p-terphenyl, 3,3'-diamino-p-terphenyl, bis(p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-bis(β-amino-t-butyl ) toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylylenediamine, p-xylylenediamine, 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, piperazine, 9,9-bis(4-aminophenyl)fluorene, 4,4'-diaminobenzanilide, 5-amino-2-(4-aminophenyl)benzimidazole, and 5-amino-2-(4-aminophenyl)benzoxazole.
[0054] As the structural unit derived from a known diamine, structural units represented by i to ix of the following formula (5) are more preferable.
[0055] [ka]
[0056] Among these, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 5-amino-2-(4-aminophenyl)benzimidazole (AI) and 5-amino-2-(4-aminophenyl)benzoxazole (AO) are exemplified as suitable ones having an excellent balance between transparency and heat resistance.
[0057] In the polyimide film of the present invention, the structural units derived from acid dianhydrides other than the structural units derived from acid dianhydrides having an ether group may be any known structural units. The structural unit derived from the known acid dianhydride is preferably pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, naphthalene-2,3,6,7-tetracarboxylic dianhydride, naphthalene-1,2,5,6-tetracarboxylic dianhydride, naphthalene-1,2,6,7-tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, naphthalene-1,2,4,5-tetracarboxylic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 1,4,5,8-tetrachloronaphthalene-2,3,6,7-tetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3'',4,4''-p-terphenyltetracarboxylic dianhydride, 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 2,3,3'',4''-p-terphenyltetracarboxylic dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3.4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, perylene-2,3,8,9-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, perylene-4,5,10,11-tetracarboxylic dianhydride, perylene-5,6,11,12-tetracarboxylic dianhydride, phenanthrene-1,2,7,8-tetracarboxylic dianhydride, phenanthrene-1,2,6,7-tetracarboxylic dianhydride, phenanthrene-1,2,9,10-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidin-2,4,5,6-tetracarboxylic dianhydride, pyrrolidin-2,5,7-tetracarboxylic dianhydride, pyrrolidin-2,6,8-tetracarboxylic dianhydride, pyrrolidin-2,7,8-tetracarboxylic dianhydride, pyrrolidin-2,8,9-tetracarboxylic dianhydride, pyrrolidin-2,9,10 ... Examples of the dianhydride include lysine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, (trifluoromethyl)pyromellitic dianhydride, di(trifluoromethyl)pyromellitic dianhydride, di(heptafluoropropyl)pyromellitic dianhydride, pentafluoroethylpyromellitic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 5,5'-bis(trifluoromethyl)-3,3',4,4'-tetracarboxybiphenyl dianhydride, 2,2',5,5'-tetrakis(trifluoromethyl)-3,3',4,4'-tetracarboxybiphenyl dianhydride, 5,5'-bis(trifluoromethyl)-3,3',4,4'-tetracarboxybenzophenone dianhydride, and trifluoromethylbenzene dianhydride.
[0058] A structural unit selected from structural units derived from tetracarboxylic dianhydrides represented by the following formula (3) is more preferred. [ka]
[0059] Among the structural units selected from the structural units derived from tetracarboxylic dianhydrides represented by the above formulae (3)-i to -iii, pyromellitic dianhydride (PMDA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) are more preferred. PMDA is even more preferred because it has good heat discoloration resistance, excellent adhesion to a substrate, can increase tensile elongation, and can lower CTE, provide excellent dimensional stability of a flexible substrate, and suppress warpage of a flexible device.
[0060] In the polyimide of the present invention, 0.1 to 5 mole units of a crosslinking component may be added to the composition in order to improve heat resistance.
[0061] The polyimide film of the present invention may be made of multiple polyimide layers. In the case of a single layer, as described above, it is preferable that the average thickness is 5 to 50 μm. In the present invention, the average thickness means a value obtained by measuring the thickness at intervals of 5 cm in each of the vertical and horizontal directions in the plane with a dial gauge or a micrometer and averaging the measured thickness. On the other hand, in the case of multiple layers, it is sufficient that the main polyimide layer is a polyimide film having the above-mentioned thickness. Here, the main polyimide layer refers to the polyimide layer that has the largest thickness ratio among the multiple polyimide layers, and its average thickness is preferably 5 to 50 μm.
[0062] The polyimide film of the present invention contains the above-mentioned preferred fluorine-containing polyimide in an amount of preferably 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more in the polyimide film.
[0063] The transparent polyimide substrate for flexible devices using the polyimide film of the present invention can be obtained, for example, by using a glass substrate as a supporting substrate, forming a polyimide film on the supporting substrate, laminating a functional layer on the transparent polyimide film, and peeling off the supporting substrate. The type of functional layer laminated on the polyimide film is not particularly limited, but includes display devices such as liquid crystal display devices, organic EL display devices, and electronic paper, as well as components of display devices such as color filters. In addition, various functional devices used in conjunction with the display devices, including organic EL lighting devices, touch panel devices, conductive films laminated with ITO, etc., gas barrier films that prevent the penetration of moisture, oxygen, etc., and components of flexible circuit boards, are also included. That is, the display element referred to in the present invention includes not only components such as liquid crystal display devices, organic EL display devices, and color filters, but also includes one or a combination of two or more of organic EL lighting devices, touch panel devices, electrode layers or light-emitting layers of organic EL display devices, gas barrier films, adhesive films, thin film transistors (TFTs), wiring layers or transparent conductive layers of liquid crystal display devices, etc.
[0064] As a method for peeling off the supporting substrate, in the case of the polyimide film of the present invention, the supporting substrate can be easily peeled off by a known method, such as by irradiating the interface between the supporting substrate (glass) and the polyimide film with laser light to peel it off, or by making an incision in the film and peeling it off.
[0065] In addition, the forming conditions of the functional layer are appropriately set according to the target flexible device, but generally, after forming a metal film, an inorganic film, an organic film, etc. on a polyimide film, it can be obtained by using a known method such as patterning into a predetermined shape or heat treatment as necessary. That is, the means for forming these display elements are not particularly limited, and for example, sputtering, deposition, CVD, printing, exposure, immersion, etc. are appropriately selected, and these process treatments may be performed in a vacuum chamber, etc., if necessary. After forming the functional layer on the polyimide film, the support substrate may be peeled off immediately after forming the functional layer through various process treatments, or it may be peeled off immediately before using it as a display device after a certain period of time has passed and the functional layer is integrated with the support substrate.
[0066] An example of a polyimide film with a functional layer in which an organic EL display element is attached on the polyimide film of the present invention is shown. First, a gas barrier layer is provided on the polyimide film of the present invention so as to prevent moisture and oxygen from passing through. Next, a circuit configuration layer including a thin film transistor (TFT) is formed on the upper surface of the gas barrier layer. In an organic EL display device, a LTPS-TFT having a high operating speed is mainly selected as a thin film transistor. In this circuit configuration layer, an anode electrode made of a transparent conductive film of, for example, ITO (Indium Tin Oxide) is formed for each of a plurality of pixel regions arranged in a matrix on the upper surface of the circuit configuration layer. Furthermore, an organic EL light-emitting layer is formed on the upper surface of the anode electrode, and a cathode electrode is formed on the upper surface of the light-emitting layer. This cathode electrode is formed in common for each pixel region. Then, a gas barrier layer is formed again so as to cover the surface of this cathode electrode, and a sealing substrate is further provided on the outermost surface for surface protection. It is desirable from the viewpoint of reliability to laminate a gas barrier layer that prevents moisture and oxygen from passing through on the surface of the sealing substrate on the cathode electrode side as well. The organic EL light-emitting layer is formed from a multilayer film (anode electrode - light-emitting layer - cathode electrode) consisting of a hole injection layer - hole transport layer - light-emitting layer - electron transport layer, etc.; however, since the organic EL light-emitting layer deteriorates due to moisture and oxygen, it is generally formed by vacuum deposition, and the layers, including the electrode formation, are continuously formed in a vacuum.
[0067] Also, an example of a polyimide film with a functional layer, in which a projected capacitive coupling type touch panel is attached onto the polyimide film of the present invention, is shown. Two electrode rows (first and second electrodes) are provided vertically and horizontally on the polyimide film of the present invention, and the change in capacitance of the electrodes is measured when a finger touches the screen, allowing precise detection of the touch position. A specific structure is a first substrate on which the first electrode is formed and a second substrate on which the second electrode is formed, joined together via an insulating layer (dielectric layer). Thinner, lighter, and more flexible devices can be achieved by replacing the substrate on which the electrodes are formed with a flexible resin substrate instead of the conventional glass substrate. Further thinner and lighter devices are also being developed by forming the first and second electrodes on a single substrate. EXAMPLES
[0068] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to these examples. It should be noted that Example 5 is a reference example.
[0069] The abbreviations of the raw materials used in the examples are shown below. (Diamine) TFMB: 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl AI: 5-amino-2-(4-aminophenyl)benzimidazole 4,4'-DAPE: 4,4'-diaminodiphenyl ether (acid dianhydride) PMDA: Pyromellitic dianhydride 6FDA: 2,2'-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride ODPA: 4,4'-oxydiphthalic dianhydride CBDA: 1,2,3,4-Cyclobutanetetracarboxylic dianhydride BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride (solvent) ·NMP: N-methyl-2-pyrrolidone
[0070] The methods for measuring and evaluating the various physical properties in the examples are as follows: [Light transmittance T500, yellowness index YI [YI(10)] and color value b*] The light transmittance at 500 nm (T500) and b* of the polyimide film (50 mm x 50 mm) were measured using a SHIMADZU UV-3600 spectrophotometer. In addition, YI (yellowness index) was calculated based on the following formula (I). Note that the T500, b*, and YI were measured at room temperature (23° C.). The same applies to YI after heating. YI=100×(1.2879X-1.0592Z) / Y (I) X, Y, and Z are the tristimulus values of the test piece and are specified in JIS Z 8722. The yellowness index (YI(10)) calculated based on a film thickness of 10 μm and represented by the following formula (II) is calculated using the YI in the above formula (I). YI(10)=YI*10 / thickness (II)
[0071] [Glass transition temperature (Tg)] A polyimide film measuring 3 mm x 15 mm was heated from 30 ° C. to 350 ° C. at a constant heating rate (5 ° C. / min) while applying a load of 30 mN in a thermomechanical analysis (TMA / SS6100) device, then cooled from 350 ° C. to 50 ° C. at a constant heating rate (10 ° C. / min), then heated from 50 ° C. to 450 ° C. at a constant heating rate (5 ° C. / min), and then cooled from 450 ° C. to 50 ° C. at a constant heating rate (10 ° C. / min), and the glass transition temperature was calculated from the inflection point of the TMA and temperature at the second heating stage. When the inflection point was not detected even when the temperature was raised to 450 ° C., it was expressed as > 450 ° C.
[0072] Coefficient of Thermal Expansion (CTE) A polyimide film measuring 3 mm x 15 mm was heated from 30°C to 350°C at a constant heating rate (5°C / min) while applying a load of 30 mN in a thermomechanical analysis (TMA / SS6100) device, then cooled from 350°C to 50°C at a constant heating rate (10°C / min), then heated from 50°C to 450°C at a constant heating rate (5°C / min), and then cooled from 450°C to 50°C at a constant heating rate (10°C / min). The thermal expansion coefficient was measured from the elongation (linear expansion) of the polyimide film during the second cooling step (350°C to 100°C).
[0073] [Tensile elongation] Test pieces of polyimide film (10 mm × 15 mm) were prepared, and tensile tests were performed using a Tensilon universal testing machine (Orientec Co., Ltd., RTA-250) at a tensile speed of 10 mm / min in accordance with IPC-TM-650, 2.4.19, to calculate the tensile elongation and tensile strength.
[0074] [Residual solvent] Approximately 0.5 mg of the cured polyimide film was heated at a rate of 20°C / min, and the NMP solvent gas generated during heating in air at 350°C for 1 hour was collected and quantitatively measured by GC-MS. The pyrolysis furnace used was a Frontier Labs PY-2020iD, and the GC-MS used was an Agilent Technologies gas chromatograph mass spectrometer, with an Agilent Technologies DB-WAX column.
[0075] Polyimide precursor solutions A to G were prepared according to the following synthesis examples.
[0076] Synthesis Example 1 Under a nitrogen stream, in a 100 ml separable flask, diamine was dissolved in NMP according to the composition in Table 1, and then acid dianhydride was added. This solution was heated at 45°C for 2 hours to dissolve the contents, and then the solution was stirred at 30°C for 50 hours to carry out a polymerization reaction, obtaining a polyimide (PI) precursor solution A (viscous solution) with a high degree of polymerization.
[0077] Synthesis Examples 2-7 As in Synthesis Example 1, Synthesis Examples 2 to 7 were carried out according to the compositions in Table 1, to obtain polyimide (PI) precursor solutions B to G (viscous solutions) with high polymerization degrees.
[0078] [Table 1]
[0079] [Table 2]
[0080] [Example 1] The polyimide precursor solution A obtained in Synthesis Example 1 was diluted with the solvent NMP to a viscosity of 4000 cP, and then coated on a glass substrate (Corning Eagle XG, size = 150 mm × 150 mm, thickness = 0.5 mm) using a spin coater so that the polyimide thickness after curing was about 10 μm. Subsequently, heating was performed at 100 ° C. for 15 minutes. Then, as shown in Table 2, in a nitrogen atmosphere (oxygen concentration: 3% or less), the temperature was raised from room temperature to 435 ° C. at a constant heating rate (4 ° C. / min), and then the temperature was held between 435 and 420 ° C. for 30 minutes, and returned to room temperature over 4 hours or more to form a 150 mm × 150 mm polyimide layer (corresponding to polyimide film A-1F) on the glass substrate, and a polyimide laminate A-1 was obtained. The imidization maximum temperature and the holding temperature for 30 minutes shown in Table 2 are values measured by measuring the temperature of the film itself. The same applies to other examples and comparative examples.
[0081] [Examples 2 to 5, Comparative Examples 1 to 5] The same procedure as in Example 1 was repeated except that polyimide precursor solution A was replaced with any of polyimide precursor solutions B to F. The imidization temperature was increased to the maximum temperature shown in Table 2, and then the temperature was held for 30 minutes at a temperature range 15°C lower than the maximum imidization temperature (however, there was no holding time in Comparative Example 1), to obtain polyimide laminates B-2 to F-5 and D-1' to E-5', respectively.
[0082] The laminates obtained in the above Examples 1 to 5 and Comparative Examples 1 to 5 were cut with a cutter along the periphery of the upper polyimide layer, immersed in water for 30 minutes, removed, wiped off the moisture, and peeled off from the glass with tweezers to obtain polyimide films A-1F to F-5F and D-1'F to E-5'F. The thicknesses of these films are shown in the thickness column of Table 2.
[0083] [Example 6] The polyimide precursor solution A obtained in Synthesis Example 1 was diluted with the solvent NMP to a viscosity of 4000 cP, and then coated on a glass substrate (Corning Eagle XG, size = 150 mm × 150 mm, thickness = 0.5 mm) using a spin coater so that the polyimide thickness after curing was about 10 μm. Then, heating was performed at 100 ° C for 15 minutes. Then, as shown in Table 2, in a nitrogen atmosphere (oxygen concentration: 100 ppm or less), the temperature was raised from room temperature to 425 ° C at a constant heating rate (4 ° C / min), and held between 425 and 430 ° C for 30 minutes, and then the temperature was raised to 450 ° C at a constant heating rate (4 ° C / min), held at that temperature for 13 minutes, and then returned to 100 ° C over 5 hours or more, air was introduced, and the sample was taken out of the nitrogen oven after returning to room temperature. A 150 mm x 150 mm polyimide layer (corresponding to polyimide film A-6F) was formed on a glass substrate to obtain polyimide laminate A-6. Note that the temperatures described here and the maximum imidization temperatures shown in Table 2 are values measured for the temperature of the film itself.
[0084] [Example 7] The curing conditions were as follows: the temperature was increased from room temperature to 415°C at a constant rate of increase (4°C / min), and the temperature was maintained between 405 and 415°C for 30 minutes, and then the temperature was increased to 465°C at a constant rate of increase (4°C / min), and the temperature was maintained between 450 and 465°C for 30 minutes. The rest of the curing conditions were the same as in Example 6, and a polyimide laminate A-7 was obtained.
[0085] [Example 8] The curing conditions were as follows: the temperature was increased from room temperature to 395°C at a constant rate of increase (4°C / min), and the temperature was maintained between 380 and 395°C for 30 minutes, and then the temperature was increased to 425°C at a constant rate of increase (4°C / min), and the temperature was maintained between 410 and 425°C for 30 minutes. The rest of the procedure was the same as in Example 6, and a polyimide laminate A-8 was obtained.
[0086] [Example 9] The curing conditions were as follows: the temperature was increased from room temperature to 155°C at a constant rate of increase (2°C / min), and the temperature was maintained at 155°C for 30 minutes, then the temperature was increased to 305°C at a constant rate of increase (3°C / min), and the temperature was maintained between 300°C and 305°C for 20 minutes, and then the temperature was increased to 415°C at a constant rate of increase (7°C / min), and the temperature was maintained between 400°C and 415°C for 30 minutes. The same procedures as in Example 6 were carried out except for the curing conditions, and a polyimide laminate A-9 was obtained.
[0087] [Example 10] The polyimide precursor solution G was used instead of the polyimide precursor solution A, and was applied so that the polyimide thickness after curing would be about 6.5 μm. The other operations were the same as in Example 8, and a polyimide laminate G-10 was obtained.
[0088] The laminates obtained in Examples 6 to 10 were cut with a cutter along the outer periphery of the portion to be peeled off, and the upper polyimide layer was left standing in air for 10 hours, and then peeled off from the glass with tweezers to obtain polyimide films A-6F, A-7F, A-8F, A-9F, and G-10F. The thicknesses of these films are shown in the thickness column of Table 2.
[0089] The polyimide films A-1F to E-5'F obtained in Examples 1 to 10 and Comparative Examples 1 to 5 were evaluated for various properties such as YI, YI(10), CTE, Tg, light transmittance at a wavelength of 500 nm (T500), b*, residual solvent, and tensile elongation. The results are shown in Table 2.
[0090] Using the polyimide glass laminates A-1 to F-5 and D-1' to E-5' obtained in Examples 1 to 5 and Comparative Examples 1 to 5, the temperature was raised to 420°C in a nitrogen atmosphere at a heating rate of 6°C / min, and then the sample was held at 420°C for 30 minutes, cooled to room temperature, and removed. As in the above, only the polyimide layer was cut along the outer periphery of the part to be peeled off with a cutter, immersed in water for 30 minutes, removed, wiped off the moisture, and peeled off from the glass with tweezers to obtain a polyimide film. The YI, YI(10) and tensile elongation after this heating were measured, and the results are shown in Table 2.
[0091] The polyimide film obtained in Example 10 had a thickness of 6.5 μm, and the yellowness index YI at that thickness was 14.3 according to the above formula (II).
[0092] The polyimide glass laminates A-6 to G-10 obtained in Examples 6 to 10 were heated to 400°C and 420°C in a nitrogen atmosphere at a heating rate of 6°C / min, and then held at that temperature for 30 minutes. The temperature was then lowered to room temperature, and the samples were taken out. As in the above, only the polyimide layer was cut along the outer periphery of the part to be peeled off with a cutter, and the polyimide film was obtained by leaving the polyimide layer in the air for 10 hours and then peeling it off from the glass with tweezers. The YI, YI(10) and tensile elongation after this heating were measured, and the results are shown in Table 2.
[0093] The 6.5 μm polyimide film obtained in Example 10 has a yellowness index YI of 14.3 after heating at 400° C. for 30 minutes.
[0094] The 6.5 μm polyimide film obtained in Example 10 has a yellowness index YI of 15.0 after heating at 420° C. for 30 minutes.
[0095] As shown in Table 2, the polyimide films according to Examples 1 to 10, which satisfied the production conditions of the present invention, had a residual solvent of 500 ppm or less, a tensile elongation of 15% or more, and a yellowness index YI of 15 or less, and after heating at 420° C. for 30 minutes, the tensile elongation was 13% or more, the yellowness index YI was 20 or less, and the films could be peeled off cleanly from the support substrate while maintaining their transparency. Therefore, such polyimide films can be suitably used as a support substrate for forming deposition masks and fan-out wafer level packages (FOWLPs) in addition to display devices such as organic EL displays, organic EL lighting, electronic paper, and touch panels. On the other hand, as shown in Table 2, the polyimide films according to Comparative Examples 1 to 5, which do not satisfy the manufacturing conditions of the present invention, contained a large amount of residual solvent, which caused the polyimide film to swell during the TFT manufacturing process and the barrier layer to partially peel off. In addition, in the case of a film with a small tensile elongation, the polyimide was torn during the laser lift-off peeling in the final process. Furthermore, the films with a YI of 15 or more and those with a YI of 20 or more after heating at 420°C for 30 minutes had poor transparency, the display became colored, and the optical effect was poor.
Claims
1. A polyimide film having a fluorine atom and an ether group in a polyimide structure, The content of structural units derived from a tetracarboxylic dianhydride represented by the following formula (3-i) is 69.994 mol % or more based on the total amount of structural units derived from a tetracarboxylic dianhydride, The residual solvent is 500 ppm or less, The yellowness index is 15 or less and the tensile elongation is 15% or more, and after heating at 420°C for 30 minutes, the yellowness index is 20 or less and the tensile elongation is 13% or more. (However, when the total amount of the polyimide film is taken as 100 mass %, the polyimide film contains 5 to 30 mass % of a structure represented by the following general formula (6)). 【Chemistry 1】 【Chemistry 2】 (In formula (6), R 1 and R 2 each independently represent a monovalent organic group having 1 to 20 carbon atoms. m represents an integer of 3 to 200.)
2. The average thickness is 5 to 50 μm, 2. The polyimide film according to claim 1, characterized in that the yellowness index, when converted into a 10 μm-thick film, is 15 or less, and the yellowness index, when converted into a 10 μm-thick film after heating at 420° C. for 30 minutes, is 20 or less.
3. 3. The polyimide film according to claim 1, having a glass transition temperature of 400° C. or higher.
4. 4. The polyimide film according to claim 1, wherein the total amount of the structural units derived from a diamine having an ether group and / or the structural units derived from a tetracarboxylic dianhydride having an ether group is 10 mol % or more based on the total amount of the structural units derived from a diamine and the structural units derived from a tetracarboxylic dianhydride.
5. 5. The polyimide film according to claim 1, wherein the structural units derived from diamines represented by the following formula (1) or (2) account for 50 mol % or more of all the structural units derived from diamines: 【Chemistry 3】 【Chemistry 4】 [wherein R in formula (1) or formula (2) 1 ~R 8 are each independently a hydrogen atom, a fluorine atom, an alkyl group or an alkoxy group having 1 to 5 carbon atoms, or a fluorine-substituted hydrocarbon group. In formula (1), R 1 ~R 4 In the formula (2), R 1 ~R 8 At least one of each of the above is a fluorine atom or a fluorine-substituted hydrocarbon group.
6. A flexible device comprising the polyimide film according to any one of claims 1 to 5, and a functional layer laminated on the surface of the polyimide film.
7. A method for producing a polyimide film, comprising using a polyamic acid solution having a fluorine atom and an ether group in a polyamic acid structure and containing 69.994 mol % or more of structural units derived from a tetracarboxylic dianhydride represented by the following formula (3)-i, based on the total amount of structural units derived from the tetracarboxylic dianhydride, applying the polyamic acid solution onto a supporting substrate so that the average thickness of the polyimide after curing is 5 to 50 μm, and then heat-treating the solution to a maximum temperature of 390 to 470° C. to effect imidization, thereby forming a polyimide film (excluding the case where the polyimide film contains 5 to 30 mass % of a structure represented by the following general formula (6) when the total amount of the polyimide film is taken as 100 mass %): 【Chemistry 5】 【Chemistry 6】 (In formula (6), R 1 and R 2 each independently represent a monovalent organic group having 1 to 20 carbon atoms. m represents an integer of 3 to 200.)
Citation Information
Patent Citations
Preparation of heat-resistant ink for ink jet printer
JP1989043579A
Polyimide precursor resin composition for flexible device substrates and method for producing flexible device using the same, and flexible device
JP2010202729A
Laminate, and utilization thereof
JP2012040836A
Polyimide precursor, polyimide, polyimide film, varnish and substrate
JP2015028143A
Polyimide precursor, polyimide, polyimide film, varnish and substrate
JP2016074915A